MUTU MANAJEMEN PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH MENENGAH - Tutik Sugesti (Hijri, 2025)
This study aims to analyze the implementation of educational management in improving the quality of learning in secondary schools. The primary focus of this research is to understand how curriculum management, human resource management, and educational facilities contribute to the improvement of students’ learning outcomes. This study employs a qualitative approach with a case study design conducted in several secondary schools in the Jakarta region. Data were collected through in-depth interviews with principals, teachers, and other educational staff, as well as direct classroom observations. The findings indicate that effective educational management—encompassing strategic planning, continuous teacher training, and the integration of educational technology—can significantly enhance the quality of learning and students’ academic achievement. Furthermore, support from school management in providing adequate facilities has a substantial impact on students’ motivation and performance. This study offers recommendations for secondary schools to further optimize educational management practices in order to achieve improved educational goals. In addition, this study emphasizes the importance of collaboration among curriculum management, teacher professional development, and the provision of adequate facilities as interrelated factors in creating an effective learning environment. With more structured management and greater attention to these aspects, secondary schools can improve the quality of education they provide and better prepare students to face global challenges..